Finite element analysis (FEA) of polylactic cid/polypropylene carbonate (PLA/PPC) blends fixation plate for craniomaxillofacial surgery - Mohamed Haneef, Intan Najwa Humaira; Shaffiar, Norhashimah; Buys, Yose Fachmi; Abdul Hamid, Abdul Malek (Emeral Insight, 2019)
Purpose – The internal fixation plate of bone fractures by using polylactic acid (PLA) has attracted the attention of many researchers, as it is biodegradable and biocompatible to the human body. However, its brittleness has led to implant fracture. On the contrary, polypropylene carbonate (PPC), which is also biodegradable and biocompatible, has an excellent elongation at break. The purpose of this paper is to compare the PLA fixation plate with the new fixation plate made up of PLA/PPC blends by using finite element analysis (FEA). Design/methodology/approach – The mandible bone from CT data set and fixation plate was designed by using the MIMICS, Amira and Solidworks softwares. Abaqus software was used for FEA of PLA/PPC fixation plate applied on the fractured mandible bone. A model of mandibular bone with a fracture in the body was subjected to incisor load. The analysis was run to determine the von Mises stress, elongation of the fixation plate and the displacement of the fractured gap of PLA/PPC blends fixation plate. Findings – The von Mises stress predicted that all the blend compositions were safe to be used as a fixation plate since the stress values were less than the yield strength. In addition, the stress value of the fixation plate was gradually decreased up to 20 percent when the amount of PPC increased to 30 percent. This indicates that the stress shielding effect was successfully reduced. The elongation of the fixation plate was gradually increased from 11.54 to 12.55 μm as the amount of PPC in the blends increased from 0 to 30 percent, thereby illustrating that the flexibility of the fixation plate was improved by the addition of PPC. Finally, the measured displacement of the fractured gap for all compositions of PLA/PPC blends fixation plate is less than 150 μm, which proves the likely success of fracture fixation by using the PLA/PPC blends. Research limitations/implications – An optimum solution of PLA/PPC blends and another new material such as compatibilizer need to be introduced in the blends in order to improve the performance of PLA/PPC blends as a new material for a fixation plate. Besides, by using the same method of producing PLA/PPC blends, longer durations for in vitro degradation of PLA/PPC blends are essential to further understand the degradation behavior of the blends applied in the human body. Finally, it is also important to further test the mechanical strength of PLA/PPC blends during the degradation period to know the current strength of the implant in the healing process of the bone.